4(x+5)-2x=5(2x+7)-3x

Simple and best practice solution for 4(x+5)-2x=5(2x+7)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+5)-2x=5(2x+7)-3x equation:


Simplifying
4(x + 5) + -2x = 5(2x + 7) + -3x

Reorder the terms:
4(5 + x) + -2x = 5(2x + 7) + -3x
(5 * 4 + x * 4) + -2x = 5(2x + 7) + -3x
(20 + 4x) + -2x = 5(2x + 7) + -3x

Combine like terms: 4x + -2x = 2x
20 + 2x = 5(2x + 7) + -3x

Reorder the terms:
20 + 2x = 5(7 + 2x) + -3x
20 + 2x = (7 * 5 + 2x * 5) + -3x
20 + 2x = (35 + 10x) + -3x

Combine like terms: 10x + -3x = 7x
20 + 2x = 35 + 7x

Solving
20 + 2x = 35 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
20 + 2x + -7x = 35 + 7x + -7x

Combine like terms: 2x + -7x = -5x
20 + -5x = 35 + 7x + -7x

Combine like terms: 7x + -7x = 0
20 + -5x = 35 + 0
20 + -5x = 35

Add '-20' to each side of the equation.
20 + -20 + -5x = 35 + -20

Combine like terms: 20 + -20 = 0
0 + -5x = 35 + -20
-5x = 35 + -20

Combine like terms: 35 + -20 = 15
-5x = 15

Divide each side by '-5'.
x = -3

Simplifying
x = -3

See similar equations:

| -4x-2=5 | | b+3b-1=15 | | 5x^2+5x-5=y | | 3x-3=3(x-8) | | 20x-5(x-1)=0 | | 7a-2=7 | | 70=3x | | (5x-2)2=17 | | x-9=34 | | 5x-9=2x-15 | | 2=3+x | | -2(5s-2)-4=-2(9s+6)-2 | | 4(6x-2)=24x-8 | | -12=4x | | 6(y+2)+y=4(y+2)-5 | | 8(n+8)=9n-1 | | 6=-2x | | 9x-9=11x | | 10-4x-6-2x=6 | | 3=y-7 | | 0.3y^2+0.4y^2-0.2y^2= | | 5.6q-5.5-5.7q=-1.1q-4.9 | | 2s-14s=84 | | 5y(2x+3)=65 | | m/8+4=16 | | 21x^2-4x-1=0 | | 12x-234=4x-10 | | 5y^2+7y^2+2=0 | | -2=3x/5+1 | | 4z+8z=z-7-5z | | 4x+2x=36 | | -9(8)-3(8)-8(6)=-7 |

Equations solver categories